The Impact Of Innovation To Company Policy Through Operation Research - Riwayadi, Eko; Murti, Tri Hesti; Young, Felina C. (Universitas Ibn Khladun Bogor, 2024)
In the ever-evolving corporate landscape, understanding how innovation influences company policies is significant for organizational success. This research investigates the complicated relationship between innovation—specifically, organizational, technological, and process innovation—and the management of critical policy domains: HR policies, compliance policies, and technological adoption policies. Leveraging surveyed data analysis, this study uncovers profound insights into the dynamic interplay between innovation strategies and policy adaptations. The study's methodology used quantitative data analysis, utilizing surveys and impact ratings to measure the influence of various innovation types on company policies. The analysis indicates that organizational innovation shows substantial influence over HR policies, underscoring the necessity of aligning HR management with the growing culture and structure of organizations undergoing transformation. Technological innovation shows as a significant motivate for adaptations in compliance policies, highlighting the critical importance of policy alignment with dynamic regulatory landscapes. Process innovation, although exhibiting a moderate impact, show cases its practical relevance in enhancing operational efficiency across all policy areas. This research extends existing literature by providing empirical evidence of innovation's multifaceted impact on policies and introduces novel perspectives, especially the influence of technological innovation on compliance policies. The implications of this study contribute in academia and practice alike, emphasizing the significance of proactive policy alignment with innovation strategies. As organizations increasingly harness innovation to remain competitive and adaptive, the research findings offer valuable guidance for optimizing the synergy between innovation initiatives and policy management, ensuring regulatory compliance, and enhancing operational efficiency.